Biocatalytic ketone reductions using Biobeads for miniaturized high throughput experimentation - Chew, Jia Shen (2022)
Miniaturized reactions conducted in parallel can lead to increased productivity in laboratories without depleting high value reagents. The use of polystyrene beads to coat thin layers of solid reagents offers an elegant strategy to tackle the microscale high throughput solid dispensing conundrum. Herein we report the successful utilization of Biobeads as the first example of high throughput reaction screening with nanomole quantities of ketoreductase on polystyrene beads for asymmetric biocatalytic reactions.